THE THREAT OF TERRORISM IN SOUTH-EAST ASIA - Н Г Рогожина (Vestnik RUDN. International Relations, 2017)
The article is dedicated to the analysis of ISIS impact on the evolution of jihadist movement in the countries of South-East Asia with implication for heightening the threat of terrorism in the region where 15% of the world Muslim population live and where long standing terrorist Islamite groups have been harboring a plan of creating a salafi caliphate for decades. The author explores the causes of vulnerability of Muslim countries of South-East Asia towards expansion of radical Islam ideology that creates prerequisites for involvement of local jihadists in the international terrorist movement with implica-tion for stability of the region. The formation of ISIS poses direct threat for security of countries of South-East Asia as it stimulates the intensification of activity of local extremist Islamic groups. They share the common position characterized by denial of democratic system of government that should be replaced by sharia governance. The attack on town Marawi (the South of the Philippines), conducted by local ex-tremists that support ISIS has become the warning for other countries of South East Asia of reinforced threat of regionalization and internalization of terrorism and of region becoming the new front of battle for ISIS planning to create its base there. The author analyses risks of growing interest of ISIS towards region where it conducts goal-directed activity aimed at expanding its social base and mobilizing its supporters while looking at the region as its main base for recruiting fighters in the context of promoting its strategy of export terrorism using “lone wolves”. For this purpose, ISIS applies different political instruments considering propaganda of jihad in Internet as the most effective way to exert ideological influence on local Muslim population. The author concludes that the formation of ISIS has resulted in renovation of terrorism in South-East Asia and emer-gence of different small terrorist cells, what leads to upgrading the level of terrorism threat in the region. The impact of ISIS on political situation in the region is displayed directly - by promoting extremism and reinforcing the threat of terrorism and indirectly - by intensifying the process of Islamic radicalization in the political development of Muslim countries of South-East Asia.